2013
DOI: 10.1017/s1092852913000217
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar depression in children and adolescents

Abstract: Children and adolescents with bipolar disorder may have depression as the presenting mood state. It is important for clinicians to distinguish between unipolar and bipolar depression in youth. Depressive episodes are common during the course of bipolar illness in children and adolescents. Evidence-based treatments are needed to guide clinicians' treatment decisions for youth with bipolar depression. This article reviews the prevalence, diagnosis, course, and treatment of bipolar depression in youth, and emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Given the need for rapid stabilization in the face of depression or suicidality, evidence for rapid treatment improvement may have important treatment implications. As the trend for treatment of bipolar depression in adults changes to emphasize primary use of mood stabilizers, it may be that the trend will similarly change for pediatric BD 27, 28 . Treatment for BD may not be consistent between children and adults, but risk for suicidality in BD is high in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Given the need for rapid stabilization in the face of depression or suicidality, evidence for rapid treatment improvement may have important treatment implications. As the trend for treatment of bipolar depression in adults changes to emphasize primary use of mood stabilizers, it may be that the trend will similarly change for pediatric BD 27, 28 . Treatment for BD may not be consistent between children and adults, but risk for suicidality in BD is high in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that youth with bipolar depression have more severe depressive episodes, associated with suicidality, hopelessness, and anhedonia compared with youth with unipolar depression,7 although further studies are required to distinguish between the two.…”
Section: Bipolar Depressionmentioning
confidence: 98%
“…Furthermore, bipolar depression is poorly understood in youth and there is a dearth of evidence-based treatments. In general, selective serotonin reuptake inhibitors are used with caution because there are limited data to suggest these agents are effective and concern that they may induce manic episodes 9,10. Also, recent meta-analyses showed that adolescent patients initiating therapy with a high dose of antidepressants seem to be at heightened risk of deliberate self-harm and that the efficacy of antidepressant therapy for youth seems to be modest 11,12.…”
Section: Introductionmentioning
confidence: 99%